1989
DOI: 10.1073/pnas.86.16.6383
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and molecular characterization of genes whose products allow Salmonella typhimurium to penetrate tissue culture cells.

Abstract: Invasion of the intestinal epithelium is thought to be an important step in the pathogenesis of Salmonella infections. Using an in vitro system, we have isolated a genetic locus, inv, that confers to a noninvasive strain of Salmonella typhimurium the ability to penetrate tissue culture cells. Highly virulent S. typhimurium strains carrying inv mutations were defective for entry into Henle-407 cells while remaining unaffected in their ability to attach to cultured cells. When administered perorally to BALB/c mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
797
5

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 895 publications
(832 citation statements)
references
References 38 publications
30
797
5
Order By: Relevance
“…This model represents a robust, widely accepted and long studied assay system (Kihlstrom, 1977). Infection of epithelial cells involves SPI-1-dependent invasion which is followed by a phase of SPI-2-dependent intracellular replication (Galan and Curtiss, 1989;Garcia-del Portillo et al, 1993). Furthermore, the HeLa-S3 cell clone has recently been suggested by the ENCODE consortium as a preferred model cell line for various experimental setups and specific culture conditions were proposed to ensure comparability between different studies (Birney et al, 2007;Dunham et al, 2012).…”
Section: Choice Of the Infection Model And Optimization Of Infection mentioning
confidence: 99%
“…This model represents a robust, widely accepted and long studied assay system (Kihlstrom, 1977). Infection of epithelial cells involves SPI-1-dependent invasion which is followed by a phase of SPI-2-dependent intracellular replication (Galan and Curtiss, 1989;Garcia-del Portillo et al, 1993). Furthermore, the HeLa-S3 cell clone has recently been suggested by the ENCODE consortium as a preferred model cell line for various experimental setups and specific culture conditions were proposed to ensure comparability between different studies (Birney et al, 2007;Dunham et al, 2012).…”
Section: Choice Of the Infection Model And Optimization Of Infection mentioning
confidence: 99%
“…Also, rough strains of Typhi lost the capability to enter epithelial cells [50] while rough mutants of Typhimurium remained invasive [51]. Epithelial cell adhesion and invasion may not be uncoupled in Typhi, since all Typhi invasion mutants isolated in recent studies [47,52] were also adhesion-defective, whereas mutants obtained from UR serotypes like Typhimurium and Enteritidis were found to adhere to cell monolayers but invaded significantly less [53][54][55]. In particular, Weinstein and colleagues have recently shown that null mutations of in A and in E genes, identified as necessary for invasion but not for adhesion in Typhimurium, abolished both properties in Typhi [47].…”
Section: Typhimentioning
confidence: 99%
“…Salmonella can invade macrophages in vitro and induce apoptosis through activation of caspase 1 by the Salmonella SipB protein encoded in the invasion locus of Salmonella pathogenicity island 1 (SPI1) (Hersh et al, 1999). Because invasion-de®cient mutants are still virulent in systemic Salmonella infections, the role of this SipB-mediated effect on macrophages is unclear in the pathogenesis of disseminated disease (Gala  n and Curtiss, 1989). OmpR, a global response regulator of a two-component regulatory system in Salmonella, is required both for macrophage cytopathology in vitro and for systemic virulence in vivo (Lindgren et al, 1996).…”
Section: Introductionmentioning
confidence: 99%